CONTROL OF HYPERTENSION IN EASTERN SAUDI ARABIA: RESULTS OF SCREENING CAMPAIGN - Al-Baghli, Nadira A. (Medknow Publications & Media Pvt Ltd, 2009)
OBJECTIVE: To assess the pattern of follow-up and level of hypertension control according to sociodemographic, and clinical risk factors in the participants of a screening campaign. RESEARCH DESIGN AND METHODS: In 2004, all Saudi residents in the Eastern Province, aged 30 years and above, were invited to participate in a screening campaign for the early detection of diabetes and hypertension. A structured questionnaire was completed during a face-to-face interview. The presence of hypertension and the place of follow-up were recorded. Blood pressure was measured by trained nurses using a mercury sphygmomanometer, according to the recommendations of The Seventh Report of the Joint National Committee on Prevention, Detection, Evaluation, and Treatment of High Blood Pressure (JNC VII). RESULTS: Thirteen point one percent of the participants had been previously diagnosed as having hypertension. In 34.3% of them, blood pressure was controlled, while 40.8% had combined uncontrolled SBP and DBP, 14.4% had isolated uncontrolled SBP, and 10.5% had isolated uncontrolled DBP. The blood pressure control was inversely associated with age. It was higher in women, singles, the educated, in those with BMI of less than 25 kg/m(2), and in those with positive history of CVD (p<0.001). CONCLUSION: Co-morbidities relevant for hypertension are very prevalent, so aggressive BP control is mandatory.